Retoryczne strategie i taktyki wywierania wpływu na wyborców w programach rosyjskich partii politycznych - Szymula, Robert (Acta Neophilologica, 2020)
The main aim of politicians’ actions (a struggle for power and retaining it) is connected with forming voters’ convictions, achieved, inter alia, with particular rhetorical strategies. Research demonstrated that in the analyzed material (programs of 11 Russian parties) three rhetorical strategies are employed: the lowering strategy, the elevation strategy and the theatricality strategy, implemented with the help of various tactics. The most frequently used strategy is undoubtedly the theatricality strategy, verbalized through the following tactics: encouraging, cooperating, separating, promising, anticipating and warning.